Microcrystalline-cellulose and polypropylene based composite: A simple, selective and effective material for microwavable packaging. (20th May 2016) - Ummartyotin, S.; Pechyen, C.
Abstract : Highlights: Cellulose and polypropylene composite was prepared. Maleic anhydride was used as coupling. Composite was employed as microwavable packaging. Abstract: Cellulose based composite was successfully designed as active packaging with additional feature of microwavable properties. Small amount of cellulose with 10 μm in diameter was integrated into polypropylene matrix. The use of maleic anhydride was employed as coupling agent. Thermal and mechanical properties of cellulose based composite were superior depending on polypropylene matrix. Crystallization temperature and compressive strength were estimated to be 130 °C and 5.5 MPa. The crystal formation and its percentage were therefore estimated to be 50% and it can be predicted on the feasibility of microwavable packaging. Morphological properties of cellulose based composite presented the good distribution and excellent uniformity. It was remarkable to note that cellulose derived from cotton can be prepared as composite with polypropylene matrix. It can be used as packaging for microwave application.